Thermal and structural characterization of the kidney stone - Firdolas, Fatih; Ates, Tankut; Bulut, Niyazi; Kaygili, Omer (Springer, 2020)
In the present study, the thermal and structural properties of a kidney stone, which was passed out of the body naturally by a 29-year-old woman who was 4 months pregnant, were investigated by using the experimental analysis methods of the differential thermal analysis (DTA), thermogravimetric analysis (TG) and X-ray diffraction. The DTA and TG analyses were taken in the temperature range of 25-1000 degrees C. After reaching the temperature of 680 degrees C, the decomposition of calcium carbonate to calcium oxide was detected. In the TG curve, the total mass loss of 26.2% was detected. The as-used kidney stone is fully composed of the single phase of calcium oxalate monohydrate (C2H2CaO5), also known as the whewellite, with the tetragonal crystal structure. The crystallinity percent of the as-used kidney stone was found to be 91.3%. The crystallite size was computed to be 107.22 +/- 4.79 nm and 79.69 +/- 3.63 nm from Scherrer and Williamson-Hall equations, respectively.
2nd International Conference on Physical Chemistry and Functional Materials (PCFM) -- JUN 25-27, 2019 -- Cappadocia, TURKEY
Keywords: Kidney stone; Differential thermal analysis (DTA); Thermogravimetric analysis (TG)